The morpho-syntax of OE verbs: The role of T(ense) and the role of v (=stem) - Castillo-Orihuela, Concepción (My University, 2023)
The paper is about the processing or computation of verbs in OE (and also verbs in the first half of the ME period). It is argued that T is the head that interprets the tau-features that expone as -d- for Past forms of weak verbs, and that v (that is, the stem) is the head that interprets the corresponding tau-features for Present and Past forms of strong verbs, that is those that expone as ablaut. As for the Present of weak verbs, it is argued that a second T head interprets corresponding features, which exhibit two notable traits: on the one hand, these features constitute a combination of tau- and phi-features; on the other hand, these features expone as the last segment for all verbal forms, that is Present and Past forms of both weak and strong verbs (which entails a situation of partial redundancy). The segment in question is the one traditionally referred to as 'subject agreement endings'. Further, I reject the analysis of Present forms of weak verbs (which would have one less segment than all other forms) as forms where 'impoverishment rules' (see the Distributed Morphology framework) apply.
Keywords: Inglés - Verbo - Morfosintaxis; OE verbs; tau-features; T head; Phi-features; V head